Manajemen Berbasis Sekolah sebagai Strategi Peningkatan Mutu Pendidikan - Lyka Rovianingrum; Syunu Trihantoyo; Eny Reosminingsih; Amrozi Khamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to explore School-Based Management (SBM) as a strategy to enhance the quality of education. Employing a qualitative approach with a multi-site case study method, this study gathered data through in-depth interviews, observations, and document analysis across several schools implementing SBM. Thematic analysis was utilized to identify patterns and themes emerging from the data. The research findings indicate that SBM grants greater autonomy to schools in managing resources and making decisions, which positively impacts educational quality. However, the implementation of SBM faces challenges such as a lack of understanding and preparedness among educators, as well as resource limitations. Active participation from all stakeholders and strong school leadership are key factors for the success of SBM. This study concludes that integrating SBM with other approaches like school autonomy, active participation, and transformational leadership is necessary to achieve optimal educational quality. Keywords: School Based Management (SBM), Educational Quality, School Autonomy, School Participation, School Leadership